A deeper insight into an intriguing acetonitrile–water binary mixture: synergistic effect, dynamic Stokes shift, fluorescence correlation spectroscopy, and NMR studies. Issue 47 (16th November 2016) - Koley, Somnath; Ghosh, Subhadip
Abstract : An insight study reveals the strong synergistic solvation behaviours from reporter dye molecules within the acetonitrile (ACN)–water (WT) binary mixture. Abstract : An insight study reveals the strong synergistic solvation behaviours from reporter dye molecules within the acetonitrile (ACN)–water (WT) binary mixture. Synergism of a binary mixture refers to some unique changes of the physical and thermodynamic properties of the solvent mixture, originating from the interactions among its cosolvents, which are absent within the pure cosolvents. Synergistic solvation of a binary mixture is likely to be fundamental for greater stabilization of an excited state solute dipole; at least to some extent greater as compared to one stabilized by any of its cosolvents alone. A dynamic Stokes shift due to the solvation of an excited dipole in the ACN–WT binary mixture is found to be highly relevant to the ground state physical properties of the solute molecule (polarity, hydrophilicity, acidity, etc. ). Largely different solvation times in the ACN–WT mixture are observed from different dye molecules with widely varying polarities. However, earlier study shows that dye molecules, irrespective of their varying polarities, exhibit very similar solvation times within a pure solvent ( J. Phys. Chem. B, 2014, 118, 7577–7785). On further study with fluorescence correlation spectroscopy (FCS) we observed that, unlike the translational diffusion coefficient ( D t ) of a dye molecule within a pure solvent, which remains the same irrespective of the location of the dye molecule inside the solvent, a broad distribution among the D t values of a dye molecule is obtained from different locations within the ACN–WT binary mixture. Lastly our 1 H NMR study in the ACN–WT binary mixture shows the existence of strong hydrogen bond interactions among the cosolvents in the ACN–WT mixture.